Composition comprising metal nanoparticles and clay

JP2025035127APending Publication Date: 2025-03-13PREMIER ANTI AGING CO LTD +1
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
JP2023141960
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Filing Date
2023-09-01
Publication Date
2025-03-13

AI Technical Summary

Benefits of technology

【0007】 本発明により、可逆的に変色して光の透過を調節できる組成物が提供される。本発明の組成物は、例えば可逆表示材料(ディスプレイ)、塗料、建材、包装、装飾等の生活資材分野に有用である。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025035127000001
    Figure 2025035127000001
  • Figure 2025035127000002
    Figure 2025035127000002
  • Figure 2025035127000003
    Figure 2025035127000003
Patent Text Reader

Abstract

To provide a composition comprising metal nanoparticles and clay.SOLUTION: Provided is a composition comprising metal nanoparticles and clay. In one embodiment, the composition further comprises an alkaline earth metal salt such as calcium carbonate or magnesium carbonate.SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a composition comprising metal nanoparticles and clay, and a hydrochromic dispersion in which the composition is dispersed in a solution. [Background technology]

[0002] Various compositions containing metal microparticles have been proposed that take advantage of the characteristics of fine metal particles. For example, it is known to obtain a composite in which precious metal microparticles are aggregated in a fluid matrix, typically smectite, and the aggregated state is stabilized (Patent Document 1). On the other hand, there is known a water-discoloring composition that absorbs liquid such as water and changes to a different appearance from its normal state, and returns to its normal state when dried (Patent Document 2). [Prior art documents] [Patent documents]

[0003] [Patent Document 1] JP 2006-184247 A [Patent Document 2] Patent No. 4433375 Summary of the Invention [Problem to be solved by the invention]

[0004] In view of the above, there has been a demand for the development of a composition that can reversibly change color in the presence of moisture to adjust light transmission.

[0005] The present inventors have found that a composition containing metal nanoparticles and clay can solve the above problems, and have completed the present invention. [Means for solving the problem]

[0006] That is, the present invention is as follows. [1] A composition comprising metal nanoparticles and clay. [2] The composition according to [1], further comprising an alkaline earth metal salt. [3] The composition according to [1] or [2], wherein the metal nanoparticles are silver nanoparticles. [4] The composition according to [1] or [2], wherein the clay is a synthetic clay. [5] The composition according to [1] or [2], wherein the alkaline earth metal salt is calcium carbonate or magnesium carbonate. [6] The composition according to [1] or [2], wherein the ratio of the major axis of the clay to the major axis of the metal nanoparticles (major axis of the clay / major axis of the metal nanoparticles) is 0.1 to 200. [7] A water-discolorable dispersion in which the composition according to [1] or [2] is dispersed in a solution. Effect of the Invention

[0007] The present invention provides a composition that can reversibly change color to adjust light transmission. The composition of the present invention is useful in the fields of living materials, such as reversible display materials (displays), paints, building materials, packaging, and decorations. [Brief description of the drawings]

[0008] [Figure 1] FIG. 13 is a diagram showing the results of measuring the transmission spectrum when a dispersion containing silver nanoparticles, synthetic smectite, and isopropanol is formed into a film. [Diagram 2] FIG. 13 is a diagram showing the results of measuring the transmission spectrum when a dispersion containing silver nanoparticles, synthetic smectite, and calcium carbonate is formed into a film. [Diagram 3] FIG. 13 is a diagram showing the results of measuring the transmission spectrum when a dispersion liquid (containing no calcium carbonate) containing silver nanoparticles and synthetic smectite was formed into a coating. [Figure 4] FIG. 1 shows the absorption characteristics of an aqueous dispersion of silver nanoparticles. [Diagram 5] FIG. 13 is a diagram showing the results of measuring the transmission spectrum when a sol prepared from a dispersion containing silver nanoparticles and synthetic smectite was formed into a film. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0009] The present invention will be described in detail below. The present invention relates to a composition comprising metal nanoparticles and clay, and also to a hydrochromic dispersion in which the composition is dispersed in a solution.

[0010] 1. Overview The present inventors were conducting research into the control of coloring of colored materials (plasmonic materials) made of precious metal particles, and in the process discovered a composition that changes color in response to an external stimulus such as exhaled breath, thereby completing the present invention. The composition of the present invention is a composite of metal nanoparticles and clay. In the embodiment, a composite of silver nanoparticles and a clay-based intercalation compound is prepared, and a composite material is devised by further combining this with calcium carbonate as a core material. It is known that calcium carbonate has a spatial cooling effect due to its absorption and scattering effect on mid- to far-infrared rays (Cell Reports Physical Science Volume 1, Issue 10, 21 October 2020, 100221). The present inventor focused on this effect (radiative cooling) and thought of combining it with metal nanoparticles. Metal nanoparticles have a selective absorption effect of near-infrared light called "plasmon," and can be used as an optimal paint base for achieving the object of the present invention.

[0011] In this invention, metal nanoparticles are first compounded with an oil-loving clay to separate (disperse) the nanoparticles at an appropriate distance, and then an alkaline earth metal salt such as calcium carbonate is added to create a three-component composite particle, which can be used to protect against exposure to harmful rays and can reduce penetration into biological tissues, thereby increasing safety to the living body.

[0012] On the other hand, a phenomenon called Surface Enhanced Raman Scattering (SERS) is known. This phenomenon is a phenomenon in which when molecules are adsorbed on a rough surface such as a precious metal, the intensity of Raman scattering is greatly amplified compared to bulk molecules. It is believed that when molecules are adsorbed on nanoparticles such as gold or silver, the amount of amplification reaches 100 times or more. The original purpose of using SERS is to detect the target specimen even at a very small concentration of the ppm or ppb order. In the present invention, this electric field enhancement phenomenon is utilized to adjust the size between the clay and the metal nanoparticles, so that even a small amount of moisture reacts to form a hydrate and change the spectroscopic characteristics. This allows the hue of the composition of the present invention to be changed or the composition to be darkened. By utilizing this color change phenomenon, it becomes possible to apply the composition as a color-changing paint for plasmonic materials. In the present invention, the color change mechanism of plasmon is based on the fact that protons derived from moisture such as breath are generated interfacially.

[0013] In the present invention, a lipophilic fine clay can be preferably used as the clay. The reason is that when it is used as a thickener for the above-mentioned combined paint, the leveling property of the film obtained is excellent. Furthermore, the coating film (coating) of the present complex utilizing fine clay particles is also excellent in the leveling property of the skin, so that it can be expected to be widely applicable in applications using coating films.

[0014] 2. Composition The composition of the present invention contains clay and metal nanoparticles and can be prepared, for example, according to the method described in WO2014 / 84026. (1) Metal nanoparticles The metal nanoparticles include any one or combination of gold, silver, copper, platinum, palladium, and rhodium. The metal nanoparticles are in the shape of a plate, the thickness of the plate being 1 nm to 50 nm, the major axis of the plate being 10 nm to 5000 nm, and the aspect ratio (ratio of length to thickness) being 3 or more. The content of the metal nanoparticles in the composition is 0.00001 to 10 wt %, and in one embodiment, it is, for example, 0.01 to 10 wt %.

[0015] The optical properties of metal nanoparticles arise from the interaction between light and electrons on the surface of the metal nanoparticles. At certain wavelengths of light, a collective oscillation of electrons on the surface of the metal nanoparticles, called surface plasmon resonance, occurs, resulting in strong absorption and scattering of light. The wavelength and frequency of the emitted light strongly depend on the size, shape, and surface modification of the metal nanoparticles. In one embodiment of the present invention, when the metal nanoparticles are silver, they can be classified as follows depending on the average major axis of the main plane. Yellow type (Y type: average major axis 20 nm or less) Magenta type (M type: average major axis approx. 35 nm) Navy type (N type: average long diameter approx. 45 nm) Indigo type (I type: average major axis approximately 50 nm) However, the metal nanoparticles used in the present invention are not limited to the above four types.

[0016] (2) Clay In the present invention, the clay is a clay-based intercalation compound, and is preferably a lipophilic clay-based intercalation compound. In the present invention, these clays are also simply called "clay". The clay-based intercalation compounds in the present invention are montmorillonite mineral group and mica mineral group. The montmorillonite mineral group has the following general formula: (X,Y) 2 ~3 Z4O 10 (OH)2·mH2O·(W1 / 3) (wherein X=Al, Fe(III), Mn(III), Cn(III), Y=Mg, Fe(II),Mn(II),Ni,Zn,Li, Z=Si, Al, W=K, Na, Ca where H2O represents interlayer water and m is an integer. It is a clay mineral represented by the formula:

[0017] Here, depending on the combination of X and Y and the number of substitutions, many types of natural products exist, such as montmorillonite, magnesian montmorillonite, iron montmorillonite, iron magnesian montmorillonite, beidellite, aluminian beidellite, nontronite, aluminian nontronite, saponite, aluminian saponite, hectorite, and sauconite. In addition to these natural products, synthetic products in which the OH group in the above formula is replaced with a halogen such as fluorine are also commercially available, and any of them can be used. Examples of mica minerals include sodium silicic mica, sodium taeniolite, and lithium taeniolite. In particular, lipophilic clay-based intercalation compounds that can be synthesized from clay-based intercalation compounds and C4-C20 alkyl quaternary ammonium cations are useful in the present invention.

[0018] Examples include smectites such as Lucentite SAN, Lucentite SAN316, Lucentite STN, Lucentite SEN, and Lucentite SPN (all trade names) manufactured by Co-op Chemical Co., Ltd., saponite (e.g., organically modified saponite) and bentonite manufactured by Kunimine Kogyo Co., Ltd., and hectorite (e.g., organically modified synthetic hectorite) manufactured by Rockwood Co., Ltd. The content of the clay in the composition is from 1.0 to less than 99.99999 wt %, and in one embodiment, for example, from 80 to 99 wt %.

[0019] The size ratio of the clay to the nanoparticles, that is, the ratio of the major axis of the clay to the major axis of the metal nanoparticles (major axis of the clay / major axis of the metal nanoparticles) is 0.1-200. In the present invention, examples of the form of a complex between metal nanoparticles and clay include a form of a complex in which clay particles smaller than the metal nanoparticles are adsorbed onto the metal nanoparticles (form a), and a form in which clay particles larger than the metal nanoparticles cover the metal nanoparticles (form b). Form a is a form in which clay particles are adsorbed onto the metal nanoparticles to form a complex (a form in which clay particles are sprinkled on the metal nanoparticles), and form b is a form in which metal nanoparticles are adsorbed onto clay to form a complex. Form b also includes a form in which the complex of form a is further adsorbed onto clay larger than the metal nanoparticles.

[0020] (3) Alkaline earth metal salts The compositions of the present invention may further include an alkaline earth metal salt. Alkaline earth metals refer to the Group 2 elements Be (beryllium), Mg (magnesium), Ca (calcium), Sr (strontium), Ba (barium), and Ra (radium), and alkaline earth metal salts refer to the sulfates, carbonates, etc. of these alkaline earth metals. In the present invention, calcium carbonate and magnesium carbonate can be preferably used. The content of the alkaline earth metal salt in the composition is 0.00001 to 99.99999 wt %, and in one embodiment of the present invention, it is, for example, 10 to 99.99999 wt %. In the composition of the present invention, the complex of metal nanoparticles and clay is surrounded by an alkaline earth metal salt.

[0021] 2. Moisture-discoloring dispersion The moisture-discoloring dispersion of the present invention is obtained by dispersing the above-mentioned composition in a solution. The solution used for producing the dispersion is mainly composed of water, and a polar solvent such as alcohol can be used. The content of the composition in the solution is 1 to 90 wt %, and in one embodiment of the present invention, it is, for example, 20 to 80 wt %.

[0022] Structural water attached to the surface of calcium carbonate, clay, etc. greatly increases absorption in the infrared region, which is not visible to the naked eye. On the other hand, interlayer water arranged in the layered structure of clay, etc., is assumed to be more physically denatured than structural water, and the electric field between the layers creates a state close to that of protons from neutral water, causing nearby plasmons to change color (significantly affecting the collective oscillation of electrons).

[0023] Here, if the size of the clay is sufficiently smaller than that of silver nanoparticles, the composition that forms the film will have a dense structure, making it difficult for gaseous water molecules to move (transport), and liquid molecules will take time to propagate through the capillaries.In contrast, if the size of the clay is coarser than that of silver nanoparticles, the card-house structure peculiar to the flat clay creates spaces (gaps) and is thought to promote the movement of exhaled breath (water vapor and its clusters). Thus, talc without interlayer ions does not cause discoloration or even adsorption of silver nanoparticles into the vicinity. EXAMPLES

[0024] The present invention will be described in more detail below with reference to examples, although the scope of the present invention is not limited to these examples.

[0025] The method for evaluating the spectral properties of the film formed when the composition was applied onto a glass slide was based on the SPF measurement method using a spectrophotometer described in the technical information "Evaluation of Sun Protection Cosmetics Using the SPF / PA Value Evaluation System" (Application Data 130-UV-0041) from JASCO Corporation, in which the diffuse transmittance of ultraviolet to infrared light in a layer of a given thickness of about 500 μm formed on a substrate was measured.

[0026] [Example 1] 1 cc of a 0.3 wt% isopropanol dispersion of synthetic smectite (Sumecton SA#2, Kunimine Industries Co., Ltd.) prepared in advance was added dropwise to 10 cc of an aqueous dispersion of silver nanoparticles (0.004 wt%) made by Ito Laboratory, mixed, and left to stand for several hours (composite formation operation). As a result, a flocculent indigo-colored precipitate was formed, taking up about one-third of the volume of the entire dispersion, and the supernatant liquid became colorless and transparent. The precipitate was collected to obtain the target complex.

[0027] 100 μL of the above complex was collected with a micropipette, spread on a 2 × 5 cm square on a slide glass, and air-dried to form a film.Then, the transmission spectrum was measured using a spectrophotometer that can handle visible to infrared light.

[0028] The results are shown in FIG. Next, about half of the film formed on the slide glass was immersed in water, immediately pulled out and shook at high speed to remove the water adhering to the surface by centrifugal force. This composite was a composition that did not change its hue in the visible to infrared range. It was also shown that the coating of the clay and silver nanoparticle composite reduces the interactions between the silver nanoparticles by isolating and dispersing them through the clay particles, thereby contributing to maintaining the plasmonic state.

[0029] For comparison, a composite was produced using an aqueous dispersion instead of isopropanol, and 1 cc of a 0.3 wt % aqueous dispersion of hydrophilic synthetic smectite (Sumecton SA, manufactured by Kunimine Kogyo Co., Ltd.) was added dropwise and the composite was prepared in the same manner as above. As a result, precipitation and aggregation were observed about 7 days after the dispersion was prepared, but it took 3 weeks for the supernatant to become colorless and transparent. Therefore, the efficiency of the composite formation was extremely poor. This indicates that the type of interlayer ion is involved in the aggregation of the complex.

[0030] [Comparative Example 1] 100 μL of the type I silver nanoparticle aqueous dispersion used in Example 1 was spread onto a slide glass in a 2×5 cm square and air-dried to form a film, after which the transmission spectrum was measured in the same manner as in Example 1. As a result, the absorption range spread over a wide region from the ultraviolet through the visible light region to the mid-infrared region, and no clear peak was observed, as shown by curve b in Figure 1. In addition, the appearance of the coating of the clay-free silver nanoparticle aqueous dispersion was a gray, non-uniform coating.

[0031] Next, about half of the film was immersed in water and immediately pulled out and swung around at high speed to shake off the water on the surface by centrifugal force, but no change in color was observed.

[0032] [Example 2] A mixture of N-type silver nanoparticles aqueous dispersion manufactured by Ito Laboratory and synthetic smectite was dropped into 10 cc of water containing 10 mg of calcium carbonate (manufactured by Fujii Pharmaceutical Co., Ltd.) while stirring. When the stirring was stopped after the dropping was completed, a blue colored precipitate was immediately formed and the supernatant liquid was colorless. The resulting blue precipitate was filtered and placed in 5 cc of water, which was then redispersed by ultrasonic irradiation to obtain the target composite. Next, a spectroscopic characteristic evaluation film was obtained by the same method as in Example 1, and then a water content test was performed.

[0033] As a result, the apparent hue of the hydrated portion changed from deep bluish purple to yellow. Figure 2 compares the spectral changes before and after the change. The absorption peak near 410 nm when air-dried (curve a shown by the blue line in Figure 2) shifted to the short wavelength side near 350 nm after hydration (curve b shown by the green line in Figure 2). Also, a notable feature of the hydrated portion was the appearance of large absorption in the infrared region near 1400 nm, and especially near 1800 nm.

[0034] All peaks returned to their original spectral state after about 20 minutes of air drying (curve c shown by the red line in Figure 2), and it was found that the water-air drying process repeatedly performed an almost reversible change; that is, the addition of water shifted the visible absorption range to the shorter wavelength side, while a large absorption appeared in the infrared range.

[0035] [Example 3] The same procedure as in Example 2 was carried out using a composition in which calcium carbonate was omitted from the recipe in Example 2. As a result, although there was no change in apparent hue due to moisture, infrared absorption was significantly enhanced as shown by curve a (green line) in Figure 3. In addition, the effect of enhancing moisture content in the infrared, similar to that of calcium carbonate, increased according to the amount of calcium carbonate added (curve b (5g) and curve c (8g) in Figure 3), confirming that the infrared absorption is enhanced in each component (particle).

[0036] [Example 4] The aqueous dispersion of silver nanoparticles (0.02 wt%) exhibits the absorption characteristics shown in Figure 4. 10 cc of this dispersion was poured into a beaker containing 1.0 g of natural smectite particles (Kunipia F: manufactured by Kunimine Kogyo Co., Ltd.) and mixed with a spatula to swell the dispersion, resulting in a transparent sol-like composite that was entirely blue-purple with a greenish tinge.

[0037] This sol was applied to a slide glass to form a film having a thickness of 500 μm using a knife edge coater capable of varying the coating thickness. After air drying, the transmission spectrum was measured in the same manner as in Example 1. The results are shown in Figure 5. The green curve a shows the spectrum when air-dried. When breath was blown onto the film from a distance of about 10 cm, the color of the film changed from blue-purple to yellow-red within a few seconds (blue curve b), but gradually returned to its original color. Furthermore, a reversible color change in response to the blowing of breath was confirmed.

[0038] [Example 5] A coating was prepared according to the same recipe as in Example 2, except that the same aqueous dispersion of silver nanoparticles was used as in Example 3. The slightly cloudy, blue-purple coating turned yellow after the impregnation (water) operation. The color showed some fading when exposed to breath. The color change response was slower than in Example 3, but this suggests that the water mobility (transport) properties in the coating composition and the type and amount of interlayer ions control the speed of color change or the degree of change.

[0039] [Comparative Example 2] The same procedure as in Example 4 was carried out except that commercially available talc (manufactured by Fujii Pharmaceuticals) was used, but no colored precipitate was formed, and the talc precipitated as it was, and the supernatant liquid remained colored and suspended. When the precipitated talc was collected and washed, it turned white. From a comparison with Example 4, it is presumed that the driving force for the composite of silver nanoparticles and clay (i.e., the force for forming interparticle bonds) is present in the ions between the clay layers (exchangeable coordination in the case of zeolite).

[0040] [Example 6] 1 cc of a 0.3 wt% isopropanol dispersion of synthetic smectite (Sumecton SA#2, Kunimine Industries Co., Ltd.) prepared in advance in the same manner as in Example 1 was added dropwise to 10 cc of an aqueous dispersion of magenta-type (M-type) silver nanoparticles manufactured by Ito Laboratory Co., Ltd., mixed, and left for several hours, at which point a reddish purple precipitate formed and the supernatant became colorless and transparent. The precipitate was collected to obtain the target composite.

[0041] [Comparative Example 3] When 100 mg of calcium sulfate powder (manufactured by Yoshino Gypsum Co., Ltd.) was added under stirring instead of the smectite used in Example 5 and allowed to stand, a black precipitate formed and the supernatant liquid became colorless and transparent. The complexation of calcium salts of strong acids significantly affected the optical properties in the visible range and impaired the aesthetics.

[0042] [Example 7] When a yellow type (Y type) silver nanoparticle aqueous dispersion (0.004 wt%) manufactured by Ito Laboratory was used to form a composite with lipophilic synthetic smectite and magnesium carbonate in the same manner and procedure as in Example 1, a yellow precipitate was formed and the supernatant liquid became colorless and transparent. The precipitate was collected to obtain the target composite.

[0043] The recovered silver nanoparticles and synthetic smectite composite were coated in the same manner as in Example 1, and a comparison was made between the presence and absence of a water-containing (immersion) operation. The above complex hardly changes when hydrated over a wide range of wavelengths, from the visible region to the near infrared region.

[0044] [Comparative Example 4] Example 7 Using the same recipe, an attempt was made to combine magnesium carbonate with 10 mg of iron oxide yellow (sold by Seiyo Kodo). The recovered precipitate was washed with water, and the washing solution was initially yellow, but became colorless after repeated washing. This indicates that silver nanoparticles are not adsorbed to oxides of heavy metals such as iron oxide.

[0045] [Example 8] Equal amounts of M-type and N-type silver nanoparticles manufactured by Ito Laboratory were mixed in advance to prepare 50cc of green water dispersion, which was then transferred to a 100cc beaker and 2.0g of natural smectite (Kunipia F: manufactured by Kunimine Kogyo Co., Ltd.) particles were added while stirring at room temperature. As a result, the mixture swelled in the beaker, and a transparent, somewhat viscous sol-like complex with a deep greenish hue was obtained. 5cc of poval-based laundry starch liquid (Kaneyonol manufactured by Kaneyo Soap Co., Ltd.) was added to this sol and stirred well, after which calligraphy paper was soaked in the pad for 1 hour, removed, and heated with an iron to make wrapping paper. When cut flowers (fresh flowers) were wrapped tightly in this wrapping paper and left overnight, some of the leaves came into contact with the paper and the contact areas faded to the point where their shapes were no longer recognizable.

[0046] The above results indicate that the components contained in the composition of the present invention act synergistically to produce the optical property of discoloration due to moisture.

Claims

1. A composition comprising metal nanoparticles and clay.

2. The composition of claim 1 further comprising an alkaline earth metal salt.

3. 3. The composition according to claim 1 or 2, wherein the metal nanoparticles are silver nanoparticles.

4. 3. The composition according to claim 1 or 2, wherein the clay is a synthetic clay.

5. 3. The composition of claim 2, wherein the alkaline earth metal salt is calcium carbonate or magnesium carbonate.

6. The composition according to claim 1 or 2, wherein the ratio of the major axis of the clay to the major axis of the metal nanoparticles (major axis of the clay / major axis of the metal nanoparticles) is 0.1 to 200.

7. A water-discolorable dispersion comprising the composition according to claim 1 or 2 dispersed in a solution.

Citation Information

Patent Citations

  • SERS substrate storage body

    JP2006184247A

  • Water-color-changing composition

    JP4433375B2